A study of local plant materials of the Malaysian wetlands in designing a tropical water garden - Dol, Mahanum (UTM, 2002)
This study has identified some potential aquatic plants and plants which can live in wet habitat, suitable for use as planting materials in the design of water garden. The plants are both native to Malaysia and non native plants which have adapted to Malaysian . Apart from plant identification in terms of origin and suitability, this study gathered information on the plants from the aspects of their benefits of use as planting material, its selection, establishment and management.